METHOD AND DEVICE FOR PROVIDING HIGH PRESSURE AND HIGH TEMPERATURE - ALEXEI IOSIFOVICH ALEXEI PRIKHNA; VALENTIN NIKOLAEVICH BAKUL; ALEXEI VLADIMIROVICH GERASIMOVICH; ALEXANDR ALEXANDROVICH SHULZHENKO (1972)
A die pair for use in high temperature high pressure apparatus for use in the synthesis of super hard materials such as diamonds, cubic boron nitride or the like in which the dies include an annular step structure on confronting cooperating faces of the dies to afford over an extended period of time stable, repetitive temperatures in the order of thousands of degrees centigrade and pressures in the order of 60 thousand atmospheres; the confronting die faces having recesses forming a pressure chamber and step structure cooperating with a deformable container of a thermo-and-electro-insulating material such as lithographic stone etc. which deforms as heated and has pressure applied thereto to form an annular sealing "burr" of a greater volume than an outer surrounding annular slot filled with a porous plastic, electro-insulating material such as "technical rubber" etc.; the deformable container being of a volume to fill the space both inwardly and outwardly of the material being treated up to the confronting edge of annular surrounding steps; the outer steps having radial, transverse slots; staggered in confronting relation; for readily accommodating the porous plastic outer seal.